A canopy radiative transfer scheme with explicit FAPAR for the interactive vegetation model ISBA‐A‐gs: Impact on carbon fluxes. Issue 2 (17th June 2013) - Carrer, Dominique; Roujean, Jean‐Louis; Lafont, Sébastien; Calvet, Jean‐Christophe; Boone, Aaron; Decharme, Bertrand; Delire, Christine; Gastellu‐Etchegorry, Jean‐Philippe
Abstract : [1] Vegetation attributes impact the Earth's carbon, water, and energy budgets by controlling the exchanges between the lower atmosphere and the continental biosphere. One of the most important factors is the distribution of the absorbed fraction of solar radiation within vegetation as it constrains the photosynthesis rate. The Interactions Surface‐Biosphere‐Atmosphere, CO2 ‐responsive (ISBA‐A‐gs) interactive vegetation model developed at Meteo‐France is particularly well designed to simulate the vegetation fluxes. A new radiation transfer scheme for the canopy has been designed and implemented in ISBA‐A‐gs, which adopts a self‐shading approach. This means that the incoming solar fluxes at the top of the canopy will hit a number of canopy layers prior to reaching the soil background. The photosynthesis model calculates the net assimilation of CO2 of each canopy layer using the absorbed photosynthetically active radiation (PAR) flux of the layer. Integration is carried out to obtain a quantitative estimate of the total net assimilation for the whole canopy layer by summing the contribution of each canopy sublayer. Assessment of the vegetation transmittance and canopy light response is then performed. Quantitative estimates of the impact on gross primary production (GPP) in local stations are presented. Also, global estimates of the fraction of absorbed PAR modeled with ISBA‐A‐gs are shown. This study demonstrates the added value of the upgraded canopy radiation transfer model for the simulation of GPP. Key Points: Canopy radiative transfer Explicit FAPAR for ISBA‐A‐gs LSM Impact on carbon fluxes